2016
DOI: 10.1167/iovs.15-18364
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Optical Coherence Tomography and Autofluorescence in the Outer Retina and Choroid of Patients With Choroideremia

Abstract: PurposeTo evaluate the relationships between RPE, photoreceptor, and choroidal degeneration in choroideremia.MethodsEnhanced-depth imaging optical coherence tomography (EDI-OCT), scanning laser ophthalmoscopy (SLO), and autofluorescence (AF) were performed on 39 patients (78 eyes) with choroideremia. The edges of surviving outer retina on OCT and residual AF were aligned. The distribution of outer retinal tubulations was mapped over a range of ages (16–71 years), and comparison made between pre- and postsubret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 23 publications
4
71
1
1
Order By: Relevance
“…1, P1, vertical arrow ) of attenuation and then loss of the IZ signal in nasal retina with approximation of the EZ to the RPE and mild ONL thinning, consistent with photoreceptor outer segment shortening (POS) and cell loss. 8,10,42-44 Further nasal to this point there is increased backscattering posterior to the RPE/BM. The structural change co-localizes with a transition of the NIR-REF signal from normal to a brighter signal near the nerve (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1, P1, vertical arrow ) of attenuation and then loss of the IZ signal in nasal retina with approximation of the EZ to the RPE and mild ONL thinning, consistent with photoreceptor outer segment shortening (POS) and cell loss. 8,10,42-44 Further nasal to this point there is increased backscattering posterior to the RPE/BM. The structural change co-localizes with a transition of the NIR-REF signal from normal to a brighter signal near the nerve (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The patient characteristics are shown in Table 1. The eyes were classified into three groups depending on the position of the anatomical fovea relative to the remaining functional visual island based on AF imaging [14,16]: (1) eyes whose fovea fell within the functional retinal island;…”
Section: Resultsmentioning
confidence: 99%
“…A caliper tool was used to measure the horizontal and vertical dimensions of the AF area extending from the centre of the fovea; these dimensions were subsequently broken down into their constituent nasal, temporal, superior and inferior parts. The horizontal and vertical dimensions of AF were used to approximate the functional visual field of each subject, the AF area being representative of the presumed surviving retina [16]. For those patients whose fovea fell outside their surviving retina, the caliper tool was used to measure the distance from the fovea to the closest edge of the surviving retina, which was assigned a negative value.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the RPE atrophy occurred before the choriocapillaris atrophy in this eye with choroideremia although the choriocapillaris might be damaged to some degree. Xue et al 11 reported that RPE loss is the primary cause of choroideremia in their study of the relationship between outer retina/choroid using OCT and RPE atrophy using FAF. Their study also supported our findings.…”
Section: Discussionmentioning
confidence: 99%